BmooMPα-III: uma metaloprotease purificada da peçonha da serpente Bothrops moojeni - Silva, Thalita Kristhina Alves (2014)
Proteolytic enzymes from bothrops venom are responsible for the majority of local and systemic effects observed during the envenomation. In this work we describe the purification and characterization of a novel metalloproteinase from Bothrops moojeni snake venom. The enzyme, denoted BmooMPα-III, was purified by a combination of ion exchange (DEAE Sephacel), molecular exclusion (Shepadex G-75) and affinity (HiTrap Chelating HP) chromatographies. BmooMPα-III enzyme represents about 0.75% of the crude venom and shows a single band with an apparent molecular mass of 26 kDa when analyzed by SDS-PAGE, under reducing conditions. BmooMPα-III cleaves first the Aα chain, then βγ, but does not hydrolyzes the γ chain of bovine fibrinogen. Inhibition of fibrinogenolytic activity by metal ion chelating agent such as EDTA allow classifies BmooMPα-III as a metalloprotease. The enzyme was inhibited by β-mercaptoethanol, however, inhibitors such as, aprotinin, leupeptin and PMSF did not Affect the fibrinogenolytic activity. The enzyme is inactive at high temperatures (≥ 60 ° C) and shows maximum activity at pH around 7.0 to 10.0. BmooMPα-III cause toxic effect on liver and kidney cells, but does not alter the cells of the lungs and heart. Preliminary results show that the enzyme BmooMPα-III induces a drastic reduction in HeLa cells and it is able to cause desfibrinating in mice when administered ip. Therefore, it is expected that this enzyme may be of medical importance as a therapeutic agent in the treatment of thrombotic disorders and cancer.